Contemporary contexts of higher medical education development: Patient-centred care in medical students' understanding - T. D. Podkladova; L. G. Smyshliaeva; A. O. Okorokov; I. I. Soshenko (Russian State Vocational Pedagogical University, 2023)
The article shows basic qualities of patient-centred care as a contemporary axiological context for the development of healthcare and higher medical education in Russia, which determines its new socio-cultural priorities. The authors have designed original educational research aimed at identifying the specificity of understanding the patient-centred care by medical students (students enrolled in specialist degree programmes). In the current research, the authors analysed the data derived from the comparative analysis of the identification attributes of doctor's patient-centredness from expert perspective and representations of these attributes in medical students' understanding. The research provides an exact representation of key meanings, principles and behavioural manifestations of a patient-centred approach in the work of contemporary doctors and proposes educational techniques to expand the content of higher medical education and eliminate the above-mentioned gaps.Aim. The research aims at identifying the specificity of understanding patient-centred care by medical students in the context of contemporary socio-cultural priorities of Russian higher medical education.Methodology and research methods. The research is based on the systemic, activity-based, phenomenological, and socio-cultural approaches. The research methods include theoretical, phenomenological, and structural types of analysis; survey method, expert assessments, and focus groups.Results. Firstly, the research has outlined the pedagogical techniques of implementing a patient-centred approach to healthcare in higher medical education, such as: a) foregrounding the problems of productive subject-to-subject interaction between doctors and patients, including their shared responsibility for taking decisions on health care treatment (such problems are to be logically distributed throughout the curricula of main educational programmes of higher medical education and integrated in each academic discipline); b) introducing a core training course of a patient-centred approach in healthcare into main educational programmes (specialist degree) to make this course a didactic system-forming axiological element of higher medical education.Secondly, the research has revealed the specificity of patient-centred healthcare as understood by medical students in terms of its meaning and implementation: 1) on the one hand, medical students support the priority of a holistic approach to patients and their problems and agree that it is essential to develop empathy and professional communicative skills, while, on the other hand, medical students demonstrate lack of readiness for the application of patient-centred approach; 2) medical students are largely unaware of patient-centred care as a joint activity of doctors and patients and its potential for involving patients into shared decision-making; 3) medical students are not taught how to provide socially contextualised care and consider patients' social environment in developing appropriate treatment plans; 4) medical students lack comprehensive understanding of patient-centred care as an integral part of educational interaction between doctors and patients; 5) medical students do not understand, or misunderstand, the value of doctors' interaction with patient communities; 6) medical students generally do not express a need to deepen and expand their ideas about patient-centred care.Thirdly, the authors have identified the educational gaps in the implementation of a patient-centred approach by medical students, namely: in understanding the fundamentals of the patient-centred paradigm in contemporary medicine; in understanding the evolution of doctor-patient interaction in terms of systemic knowledge about the patient-centred care criteria and behaviours in the work of contemporary clinicians; in understanding the principles and methods of productive interaction between medical and patient communities; in practicing educational interaction with patients. Finally, the authors have determined and articulated the demand of medical student for a more varied and extended interaction with their educators on the problems of patient-centred healthcare within main educational programs of higher medical education. The authors have explicated the need to foreground patient-centred issues of healthcare in the content of higher medical education, by means of including mandatory communication and training formats for teaching methods of patient-oriented communicative, emotional and educational interaction between doctors and patients.Scientific novelty. It has been proven that patient-centred care has become a topical socio-cultural context for the development of Russian higher medical education. The research specifies the educational gaps medical students encounter in developing their competencies in solving the problems of patient-centred healthcare. The authors have designed teaching methods that would promote the integration of patient-centred care into higher medical education.Practical significance. The research findings can be used for the development of higher medical education didactics, namely to expand the curricula and upgrade the management of main educational programmes as well as to improve the curricula of the extended pedagogical education programmes of higher medical education.